Answer :
[tex]x^2-5x+6=0[/tex]
[tex]x=\frac{-(-5)\pm\sqrt{(-5)^2-4\times1\times6}}{2\times1}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{5\pm\sqrt{25-4\times6}}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{5\pm\sqrt{25-24}}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{5\pm\sqrt{1}}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{5\pm1}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{5-1}{2}\;\;\;\vee\;\;\;x=\frac{5+1}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=\frac{4}{2}\;\;\;\vee\;\;\;x=\frac{6}{2}\Leftrightarrow[/tex]
[tex]\Leftrightarrow x=2\;\;\;\vee\;\;\;x=3[/tex]
Answer: [tex]x\in\{2\;;\;3\}[/tex]
[tex]\sf\dfrac{-(-5)\pm\sqrt{\sf (-5)^2-4\cdot1\cdot6}}{2\cdot1}[/tex]
[tex]\sf\dfrac{5\pm\sqrt{\sf 25-24}}{2}[/tex]
[tex]\sf\dfrac{5\pm\sqrt{\sf 1}}{2}[/tex]
[tex]\sf\dfrac{5\pm1}{2}[/tex]
[tex]\sf x'=\dfrac{5-1}{2}~~~~~~x''=\dfrac{5+1}{2}[/tex]
[tex]\sf x'=\dfrac{4}{2}~~~~~~~~~~~~x''=\dfrac{6}{2}[/tex]
[tex]\sf x'=2~~~~~~~~~~~~~x''=3[/tex]
⠀⠀
Solutions = {2, 3}
⠀⠀
⠀⠀
I hope that helps !!